Investigation and practical applying of peculiarities of time dependent variations of humane color preferences with using BIOCOLOR - Madyar, S.-A. I.; Kovalevskaya, E. E.; Moiseenko, E. V. (Ukrainian Antarctic Journal, 2012)
Comparative analysis of human color preference relations proved to be an important research area within the theory of color dynamics. To sum up the results of these research activities it can be established, that the comparison of the index system of color preferences – containing variations in time of color preference values– and the color scale of the spectrum being constant in time has provided new approximations to evaluate psychophysiology and psychology of color adaptation. Investigation of the effects of colors on physiology parameters by comparing color preference values has led to the development of an auxiliary tool of color adaptation. Applying the color preference index system, established by Dr. Antal Nemcsics, as the comparable etalon facilitating analysis of color preference/relaxation reactions observable under different circumstances and human states.